2005
DOI: 10.1158/0008-5472.can-04-3947
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging Visualization of Hyaluronidase in Ovarian Carcinoma

Abstract: Hyaluronan, a high molecular weight, negatively charged polysaccharide, is a major constituent of the extracellular matrix. High molecular weight hyaluronan is antiangiogenic, but its degradation by hyaluronidase generates proangiogenic breakdown products. Thus, by expression of hyaluronidase, cancer cells can tilt the angiogenic balance of their microenvironment. Indeed, hyaluronidase-mediated breakdown of hyaluronan correlates with aggressiveness and invasiveness of ovarian cancer metastasis and with tumor a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 40 publications
1
62
0
Order By: Relevance
“…Unfortunately, the normal spread of relaxation times was too high and unspecific to allow cancer identification using these variables. A large number of Gd-labeled vector molecules have also been suggested as markers for cancer by 1 H MRI (28). All these molecules are designed to fit into receptors on the cell surface.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the normal spread of relaxation times was too high and unspecific to allow cancer identification using these variables. A large number of Gd-labeled vector molecules have also been suggested as markers for cancer by 1 H MRI (28). All these molecules are designed to fit into receptors on the cell surface.…”
Section: Discussionmentioning
confidence: 99%
“…146 Hyaluronidase activity was detected by MRI in an ovarian tumor model to assess peritumor angiogenic balance. 152 Until today, targeted contrast agents used for molecular imaging by MRI have only been used in preclinical applications, however, the proof of principle studies in preclinical settings have opened avenues for novel targets for MRI in the clinical assessment of cancer patients.…”
Section: Molecular Imaging With Mri In Cancer Imagingmentioning
confidence: 99%
“…67 Mazooz et al 68 described a Gd-DTPA peptide acting as a transglutaminase substrate, which was used to monitor transglutaminase activity. Shiftan et al reported MR imaging visualization of hyaluronidase in ovarian carcinoma, 69 related to the aggressiveness of ovarian cancer metastasis. Chen et al 70 visualized plaque rupture in atherosclerosis with a Gd-DOTAϪ serotonin derivative, which polymerizes in the presence of neutrophil myeloperoxidase, resulting in a remarkable relaxivity increase.…”
Section: Ph-sensitive Probesmentioning
confidence: 99%